Peningkatan Kinerja Kelompok Simpan Pinjam melalui Pelatihan Administrasi Koperasi, Komunikasi Persuasive dan Kewirausahaan - Yuli Kurniyati (Jurnal Maksipreneur, 2012)
The Problems in Credits and savings groups of ”kopsa” and “Melati” 1). System administration and financial management is very simple, 2) The low productive business activities (entrepreneurship) members, 3) Not having a clear institutional rules, 4). Persuasive communication skills owned by the board and members are still low. The method used to overcome these problems is the partner outreach, training and consultation conducted consisting of a persuasive communications training, administration and accounting in cooperative training, entrepreneurship training and computer training and extension procedures for obtaining legal cooperation. Participant training consists of officials from the each partner. The result of this activity is the increase of knowledge, understanding and skills of participants in the field of persuasive communication, administration and accounting cooperatives, entrepreneurship and the use of computers to support the operations of savings and loan it can be seen from the indicators: 1). completion of the annual financial statements of each group covering Balance Sheet, SHU reports and cash statements . 2) flow increased motivation to self-employed members marked the emergence of several new businesses 3) completion of AD / ART as a basic rule group 4) improved communication skills board and behavioral changes that gave rise to productive attitude.